Comparative law and equivalence assessment of system-bound terms in EU legal translation - Jopek-Bosiacka, Anna (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2013)
<!--[if gte mso 9]> Normal 0 21 false false false MicrosoftInternetExplorer4 <![endif]--> Legal translation is not only inter-lingual translation, but also a translation of and between various legal systems. Many translation problems may be solved by having reference to comparative law. This is especially critical in the European Union, whose policy of multilingualism and striving towards the principle of equal authenticity in law leads to something close to mission impossible: the reconciliation of the 28 legal systems of its member states into a coherent body of law which would ensure uniform interpretation of EU legal texts. The aim of this paper is to describe legal translation strategies in general, and illustrate them using English–Polish official translations of system-bound terms of the case law of the European Court of Justice. The analysis will focus on several vital concepts of common law, such as ‘equity’, ‘consideration’, ‘trust’, ‘misrepresentation’, and ‘tort’; terms which are mostly absent in the Polish legal system. Comparative law will serve as a tool for the quality assessment of legal translation and evaluation of the equivalence of legally adequate terms. <!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:Standardowy; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman"; mso-ansi-language:#0400; mso-fareast-language:#0400; mso-bidi-language:#0400;} --> <!--[endif] -->